2023
DOI: 10.1108/jabes-08-2022-0205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of economic policy uncertainty on financial flexibility before and during the COVID-19 pandemic

Tamanna Dalwai

Abstract: PurposeThis study examines the influence of economic policy uncertainty on financial flexibility before and during the coronavirus disease 2019 (COVID-19) pandemic. Few prior studies have examined this association specifically for debt and cash flexibility.Design/methodology/approachUsing quarterly data from 2016 to 2022, 1014 observations were collected from the S&P Capital IQ database for listed tourism companies in India. The pre-pandemic period is defined as 2016 Q1 to 2020 Q1, whereas the pandemic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Our study uses three measures of cash holdings. The first variable of CashHolding is measured as the natural logarithm of one plus cash and cash equivalents (Dalwai, 2023; Deshmukh et al , 2021; Foley et al , 2007). This measure is considered the most efficient to alleviate the problem of large outliers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study uses three measures of cash holdings. The first variable of CashHolding is measured as the natural logarithm of one plus cash and cash equivalents (Dalwai, 2023; Deshmukh et al , 2021; Foley et al , 2007). This measure is considered the most efficient to alleviate the problem of large outliers.…”
Section: Methodsmentioning
confidence: 99%
“…Intellectual capital (IC) is an assimilation of knowledgebased resources such as business ideas, skills and infrastructure (Yang and Lin, 2009) that plays a leading role in the sustainable development of firms (Reed et al, 2006). IC is known to improve a firm's financial and organizational performance (Habib and Dalwai, 2023;Dalwai A crosscountry study and Salehi, 2021;Rehman et al, 2022;Xu et al, 2022), financial health and credit rating (Guim on, 2005;Dalwai and Sewpersadh, 2023) and contribute to the overall economy (Lev and Gu, 2016). High IC efficiency is associated with low financial leverage (D'Amato, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…When a company possesses financial flexibility, it is better equipped to address unexpected challenges, such as economic downturns or unforeseen market fluctuations. By using more cash and paying less cash dividends, a company pursuing a financial flexibility strategy can respond well to economic shocks such as financial crises (Arslan-Ayaydin et al, 2014; Bancel & Mittoo, 2011; Fahlenbrach et al, 2020) or periods of economic uncertainty (Dalwai, 2023; Yousefi & Yung, 2022). Yousefi and Yung (2022) also found that financial flexibility enables firms to avoid financial distress.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This special issue spans a wide array of topics, from the pandemic’s impact on financial systems (Dalwai, 2023) in both developed and developing economies to the nuanced intersections of religious beliefs and international trade. These concerns, while paramount currently, have enduring relevance.…”
mentioning
confidence: 99%